The impact of perceived usefulness of mobile learning on skills development: the mediating role of cognitive load in JPPH, Kota Bharu - Abdullah Thani, Ayu Kamareenna; Rosely, Nurhidayah; Alias, Noor Rahmawati; Nik Mohd Zainordin, Nik Mohamad Shamim; Ismail, An Nur Nabila (Penerbit UiTM (UiTM Press), 2025)
This pilot study explores the influence of the perceived usefulness of mobile learning on skills development among government servants in the Valuation and Property Services Department (JPPH) in Kota Bharu, with cognitive load examined as a mediating variable. As mobile learning tools become increasingly integral to professional development in the public sector, understanding how employees perceive their usefulness can provide insights into the effectiveness of these tools for skill acquisition. Perceived usefulness, defined as the degree to which users believe that mobile learning improves their job performance, is posited to influence skills development directly and indirectly through cognitive load. Cognitive load, or the mental effort required to process new information, may either facilitate or inhibit learning effectiveness depending on its level. Thirty department staff members participated in this pilot study to evaluate the extent to which perceived usefulness influences skill development and how cognitive load impacts this relationship. The study’s findings aim to inform future training approaches that utilise mobile learning for efficient and accessible skills development, ultimately enhancing departmental performance in property valuation and management.